2011
DOI: 10.1073/pnas.1013814108
|View full text |Cite
|
Sign up to set email alerts
|

Brain-state–independent neural representation of peripheral stimulation in rat olfactory bulb

Abstract: It is critical for normal brains to perceive the external world precisely and accurately under ever-changing operational conditions, yet the mechanisms underlying this fundamental brain function in the sensory systems are poorly understood. To address this issue in the olfactory system, we investigated the responses of olfactory bulbs to odor stimulations under different brain states manipulated by anesthesia levels. Our results revealed that in two brain states, where the spontaneous baseline activities diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 62 publications
(79 reference statements)
3
28
0
1
Order By: Relevance
“…This result agrees well with previous observations from other cortical sensory systems, using a variety of neuroimaging techniques [e.g., functional MRI (fMRI), optical imaging, and electrophysiology (2-9)]. Taken together, these studies (1)(2)(3)(4)(5)(6)(7)(8)(9) imply that there may be inherent neuronal mechanisms to ensure a similar level of information transfer from sensory input, regardless of external/internal situations that may impact the brain's baseline state (10).…”
supporting
confidence: 81%
See 3 more Smart Citations
“…This result agrees well with previous observations from other cortical sensory systems, using a variety of neuroimaging techniques [e.g., functional MRI (fMRI), optical imaging, and electrophysiology (2-9)]. Taken together, these studies (1)(2)(3)(4)(5)(6)(7)(8)(9) imply that there may be inherent neuronal mechanisms to ensure a similar level of information transfer from sensory input, regardless of external/internal situations that may impact the brain's baseline state (10).…”
supporting
confidence: 81%
“…A descriptive example, as shown in Fig. 1A and which is comparable to data presented by Li et al (1), illustrates behavior of a neuronal population (Fig. 1A, Left) as well as its dynamic pattern (Fig.…”
Section: Relationship Between Neuroimaging Signal and Neuronal Activitysupporting
confidence: 58%
See 2 more Smart Citations
“…Additionally, investigation by Xu and colleagues (Wuhan Institute of Physics and Mathematics, Chinese Academy of Sciences) indicated that the M/T cells can encode the odor locations [17]. Their further work suggested the neural representation of peripheral stimulation in rat OB is independent of brain state [18].…”
mentioning
confidence: 99%